A Longitudinal Study of the Temporal Relation Between Problem Gambling and Mental and Substance Use Disorders Among Young Adults. (February 2016) - Afifi, Tracie O.; Nicholson, Ryan; Martins, Silvia S.; Sareen, Jitender
Objective: Relatively little is known about the temporal relation between at-risk gambling or problem gambling (PG) and mental and substance use disorders (SUDs) in young adulthood. Our study aimed to examine whether past-year, at-risk, or PG is associated with incident mental disorders and SUDs (that is, depression, generalized anxiety disorder, obsessive–compulsive disorder [OCD], or alcohol dependence) and illegal drug use, and whether past-year mental disorders and SUDs and illegal drug use is associated with incident at-risk or PG. Method: Data for this longitudinal study were drawn from the Manitoba Longitudinal Study of Young Adults (MLSYA). Respondents aged 18 to 20 years in 2007 were followed prospectively for 5 years. Results: In cross-sectional analyses, at-risk or PG was associated with increased odds of depression, OCD, alcohol dependence, and illegal drug use. In longitudinal analysis at-risk or PG at cycle 1 was associated with incident major depressive disorder, alcohol dependence, and illegal drug use in the follow-up period. Only illegal drug use at cycle 1 was associated with incident at-risk or PG during follow-up. Conclusions: At-risk or PG was associated with more new onset mental disorders and SUDs (depression, alcohol dependence, and illegal drug use), compared with the reverse (illegal drug use was the only association with new onset at-risk or PG). Preventing at-risk or PG from developing early in adulthood may correspond with decreases in new onset mental disorders and SUDs later in adulthood.